PROCEEDINGS OF THE SOCIETY OF BRITISH NEUROLOGICAL SURGEONS: 56th MEETING (1958)
The 56th meeting of the Society of British Neurological Surgeons was held in London on November 15 and 16, 1957. The Society met at the London Hospital on November 15, with the President, W. R. Henderson (Leeds), in the chair and held a combined meeting with the Association of British Neurologists on November 16 at the National Hospital, the two Presidents, W. R. Henderson (Leeds) and Sir Charles Symonds (London), occupying the chair in rotation.